2010
DOI: 10.1002/jbmr.15
|View full text |Cite
|
Sign up to set email alerts
|

A nonsecosteroidal vitamin D receptor ligand with improved therapeutic window of bone efficacy over hypercalcemia

Abstract: Vitamin D 3 analogues were shown to be beneficial for osteoporosis and other indications, but their narrow therapeutic window between efficacy and hypercalcemia has limited their clinical utility. A nonsecosteroidal, tissue-selective, orally bioavailable, vitamin D receptor (VDR) ligand was ascertained to be efficacious in bone while having modest calcemic effects in vivo. This compound (VDRM2) potently induced Retinoid X Receptor alpha (RXR)-VDR heterodimerization (EC 50 ¼ 7.1 AE 1.6 nM) and induced osteocalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…It was generally well tolerated and restored bone mass, spatial architecture, and bone strength, but it was not as potent as ED71 or 1,25-(OH) 2 D 3 . However, hypercalcemia was not observed in animals until 4.6 mg/kg, indicating a therapeutic safety margin of 57-fold between bone efficacy and hypercalcemia, which is significantly greater than ED-71, 1,25-(OH) 2 D 3 , and alfacalcidol (Sato et al, 2010). If the data from this study are relevant to the clinical trials with ED-71, VDRM2 may have clinical efficacy to treat osteoporosis as well as other disorders, either alone or in combination with other approved therapies.…”
Section: Vitamin D Receptor Modulatorsmentioning
confidence: 90%
See 1 more Smart Citation
“…It was generally well tolerated and restored bone mass, spatial architecture, and bone strength, but it was not as potent as ED71 or 1,25-(OH) 2 D 3 . However, hypercalcemia was not observed in animals until 4.6 mg/kg, indicating a therapeutic safety margin of 57-fold between bone efficacy and hypercalcemia, which is significantly greater than ED-71, 1,25-(OH) 2 D 3 , and alfacalcidol (Sato et al, 2010). If the data from this study are relevant to the clinical trials with ED-71, VDRM2 may have clinical efficacy to treat osteoporosis as well as other disorders, either alone or in combination with other approved therapies.…”
Section: Vitamin D Receptor Modulatorsmentioning
confidence: 90%
“…In addition, these agents are not orally bioavailable and do not rebuild bone once it has been lost. With this in mind, Sato et al (2010) identified VDRM2, Nuclear Receptors and Their Selective Modulators a nonsecosteroidal, tissue-selective, orally bioavailable VDR ligand. This analog induced VDR-RXR heterodimerization (EC 50 7.1 nM) and stimulated the expression of the bone genes (osteocalcin) in a manner similar to ED-71 and alfacalcidol.…”
Section: Vitamin D Receptor Modulatorsmentioning
confidence: 99%
“…With respect to serum calcium ( Figure 2C), treatment with LY627-2K results in a modest increase across the dose range. Treatment with LY627-2K, within the tested dose range, does not result in hypercalcaemia, i.e., values above the normal threshold level (112 mg·L À1 ) in this model (Sato et al, 2010).…”
Section: In Vitro Identification Of Active Pth Ligandsmentioning
confidence: 64%
“…78.3), it contains a novel amide side chain, displays good affinity for VDR (K i ¼ 57.8 nM), and is a potent inducer of RXR-VDR heterodimerization (EC 50 ¼ 7.1 nM). VDRM2 induces osteocalcin-promoter activity with an EC 50 of 1.9 nM as compared to 1.3 nM for 1a,25(OH) 2 D 3 , while being less potent in calcium channel TRPV6 upregulation than 1a,25(OH) 2 D 3 with an EC 50 of 37.2 nM compared to that of 0.6 nM for 1a,25(OH) 2 D 3 [15].…”
Section: Identification Structure and Biological Characterizationmentioning
confidence: 87%